Seasonal cycles of assortative mating and reproductive behaviour in polymorphic populations of Harmonia axyridis in China - Wang, Su; Michaud, J. P.; Zhang, Runzhi; Liu, Shuang; Zhang, Fan (My University, 2009)
1. We observed native populations of Harmonia axyridis (Pallas) around Beijing, China, over 2 years and performed choice and no-choice mating tests between melanic and succinic (non-melanic) beetles in the laboratory. 2. Succinic phenotypes outnumbered melanics by 5:1 in autumn, but melanics became equally abundant in spring, supporting previous inferences that melanism is advantageous in winter, but costly in summer. 3. Female H. axyridis expressed mate preference overtly, by rejecting less-preferred phenotypes, and cryptically, by retaining their eggs for longer periods after matings with less-preferred males, ostensibly to replace their sperm. 4. Succinic pairs formed more quickly in the spring generation, and melanic pairs in the autumn, and the time to copula was affected by both male and female phenotype. The strength of mate preference was contingent on female phenotype, suggesting melanic alleles had pleiotropic effects. 5. Whereas pair formation was under female control, the duration of copula was under male control and lasted longer in the autumn generation than in the spring. Copulations in the choice test tended to be shorter between similar phenotypes, suggesting that males invested more in dissimilar females when alternative mates were available. 6. Although spring and autumn generations were raised under identical conditions, significant contrasts were observed in their reproductive behaviour. 7. Two alternative hypotheses are advanced to explain why gender-specific reproductive behaviours might vary between generations: maternally-mediated epigenetic factors that influence the expression of genes in progeny as a function of maternal environment, and linkage disequilibria among alleles that cycle in frequency seasonally as a function of assortative mating.
Citation: Wang, S., Michaud, J.P., Zhang, R., Liu, S., & Zhang, F. (2009). Seasonal cycles of assortative mating and reproductive behaviour in polymorphic populations of Harmonia axyridis in China. Retrieved from http://krex.ksu.edu
Keywords: Coccinellidae; Female choice; Mate preference; Melanism; Polymorphism; Seasonality; Sperm competition